Restoring the rule of law to public administration: what Frank Goodnow got right and Leonard White didnot - Lynn, Laurence E., Jr. (2009)
Although the rule of law is universally regarded as a fundamental principle of democratic governance, the field of public administration continues to exhibit the "anti-legal temper" that emerged in the 1920s, when Leonard White's managerialism largely displaced Frank Goodnow's emphasis on the intimacy of law and administration. Although administrative law is a distinguished subfield of scholarship and practice within public administration, the consensus view within the profession seems to be that law is one of many constraints on administrative discretion rather than its source, a challenge to administrative leadership rather than its guiding principle. In addition to unacceptably narrowing the range of values influencing public administration, such a view undermines the profession's ability to contribute to the design of our governance arrangements at a time when constitutional institutions are being seriously challenged. To fulfill its constitutional role, public administration must commit itself to the rule of law as an institution that secures its legitimacy. - Reproduced.
Keywords: Rule of law; Public administration